Elective reconstruction of thoracoabdominal aortic aneurysm type IV by transabdominal approach - Marjanović Ivan; Jevtić Miodrag; Mišović Sidor; Šarac Momir (Vojnosanitetski Pregled)
Introduction. Thoracoabdominal aortic aneurysm (TAAA) type IV represents an aortic dilatation from the level of the diaphragmatic hiatus to the iliac arteries branches, including visceral branches of the aorta. In the traditional procedure of TAAA type IV repair, the body is opened using thoractomy and laparotomy in order to provide adequate exposure of the descending thoracic and abdominal aorta for safe aortic reconstruction. Case report. We reported a 71-yearold man with elective reconstruction of the TAAA type IV performed by transabdominal approach. Computed tomography scans angiography revealed a TAAA type IV with diameter of 62 mm in the region of celiac trunk and superior mesenteric artery branching, and the largest diameter of 75 mm in the infrarenal aortic level. The patient comorbidity included a chronic obstructive pulmonary disease and hypertension, therefore he was treated for a prolonged period. In preparation for the planned aortic reconstruction asymptomatic carotid disease (occlusion of the left internal carotid artery and subtotal stenosis of the right internal carotid artery) was diagnosed. Within the same intervention percutaneous transluminal angioplasty with stent placement in right internal carotid artery was made. In general, under endotracheal anesthesia and epidural analgesia, with transabdominal approach performed aortic reconstruction with tubular dakron graft 24 mm were, and reimplantation of visceral aortic branches into the graft performed. Postoperative course was uneventful, and the patient was discharged on the postoperative day 17. Control computed tomography scan angiography performed three months after the operation showed vascular state of the patient to be in order. Conclusion. Complete transabdominal approach to TAAA type IV represents an appropriate substitute for thoracoabdominal approach, without compromising safety of the patient. This approach is less traumatic, especially in patients with impaired pulmonary function, because there is no thoracotomy and any complications that could follow this approach.